Gender Work: A Sequential-Categorial Analysis of Moroccan Mundane Conversations and Calls to Phone-in Programs - Bouhout Najib (Université Sidi Mohamed Ben Abdellah, Faculté des Lettres et Sciences Humaines - Dhar El Mehraz -, Fès, 2018)
Research on gender and language has been through a recent crisis. The study of ‘difference’ has no longer any appeal since its drawbacks were exposed. In fact, many scholars attacked its inherent essentialism and its unjustified focus on ‘differences’ to the exclusion of other interesting phenomena. Added to this attack is the wider currency of constructionism: constructionists argue for the centrality of the performative qualities of language for the situated construction of gender identities. The framework allows an investigation of gender as a responsive and intersubjective process in talk. In order to study societal members’ orientation to the intersubjective character of gender, researchers have recently drawn on the principles of Conversation Analysis and Membership Categorization Analysis, especially as their tools pay close attention to the local and performative character of identities in situ in the immediate context offered by talk as the site of multiple forms of sequential and categorial organizations. Both approaches take Ethnomethodology other stands of interactionism as their theoretical foundation. The former particularly goes to great length in insisting on the situated, local, and interactional basis of all forms of social institutions. Ethnomethodology is especially known for its reluctance to draw on external social structures, seeing these as brought off by social members’ common sense practical methods rather than vice versa. One such aspect of common sense practices is taken up here. The sequential and categorial aspects of Moroccan members’ work in talk are traced in order to see how gender gets constructed, negotiated and sustained; and what the consequences are for such work. Recordings of naturally occurring data in the form of mundane talk and calls to radio-phone programs are used. The recordings were transcribed and their sequential and categorial aspects investigated. Two results of the investigation stand out. First, Moroccans draw on default gender categories, i.e., common sense, to achieve a particular type of gender identity. However; common sense gender categories are not static, but can be used to organize members’ conversational moves to bring off particular outcomes. Gender identity work is inextricably tied to the performative nature of talk. It is, in short, a discursive achievement. Second, and relatedly, Moroccan societal members bring gender categorization to bear on everyday moral dilemmas they face in ordinary life. Their categorial work reflexively constructs gender identities as well as exploits these to make sense of moral issues. The details of gender work are discussed, its nuisances and implications are listed, and its applications are then considered.
Keywords: Gender construction; Identity; Morality; Conversation analysis; Membership categorization; Telephone calls; Ethnomethodology